The Tomato (Solanum Lycopersicum cv. Micro-Tom) Natural Genetic Variation Rg1 and the DELLA Mutant Procera Control the Competence Necessary to Form Adventitious Roots and Shoots - Lombardi-Crestana, Simone; Azevedo, Mariana da Silva; Ferreira e Silva, Geraldo Felipe [UNESP]; Pino, Lilian Ellen; Appezzato-da-Gloria, Beatriz; Figueira, Antonio; Nogueira, Fabio Tebaldi Silveira [UNESP]; Pereira Peres, Lazaro Eustaquio (Oxford University Press, 2012)
Despite the wide use of plant regeneration for biotechnological purposes, the signals that allow cells to become competent to assume different fates remain largely unknown. Here, it is demonstrated that the Regeneration1 (Rg1) allele, a natural genetic variation from the tomato wild relative Solanum peruvianum, increases the capacity to form both roots and shoots in vitro; and that the gibberellin constitutive mutant procera (pro) presented the opposite phenotype, reducing organogenesis on either root-inducing medium (RIM) or shoot-inducing medium (SIM). Mutants showing alterations in the formation of specific organs in vitro were the auxin low-sensitivity diageotropica (dgt), the lateral suppresser (ls), and the KNOX-overexpressing Mouse ears (Me). dgt failed to form roots on RIM, Me increased shoot formation on SIM, and the high capacity for in vitro shoot formation of ls contrasted with its recalcitrance to form axillary meristems. Interestingly, Rg1 rescued the in vitro organ formation capacity in proRg1 and dgtRg1 double mutants and the ex vitro low lateral shoot formation in pro and ls. Such epistatic interactions were also confirmed in gene expression and histological analyses conducted in the single and double mutants. Although Me phenocopied the high shoot formation of Rg1 on SIM, it failed to increase rooting on RIM and to rescue the non-branching phenotype of ls. Taken together, these results suggest REGENERATION1 and the DELLA mutant PROCERA as controlling a common competence to assume distinct cell fates, rather than the specific induction of adventitious roots or shoots, which is controlled by DIAGEOTROPICA and MOUSE EARS, respectively.
Keywords: Cell fate; competence; determination; hormonal mutants; Micro-Tom; plant development; regeneration